Entrepreneurship Training : "Strategy To Increase Sales Through Attractive Product Packaging” At Umkm Desa Gumukrejo Teras Boyolali” - Yuli Chomsatu (International Journal of Community Service Implementation, 2023)
Many MSME products are still difficult to compete due to the many obstacles faced by SMEs. One of them is the lack of information about the importance of packaging to product marketing. The Mindset of MSME actors in Gumukrejo Village Teras Boyolali most still do not consider that the packaging of the products produced is important to increase sales. Changing the mindset about the importance of attractive Packaging is very necessary for MSME actors in Gumukrejo Village today. So that the results of this training are expected to be able to change the Mindset for MSMEs to be able to do attractive packaging for the products they produce to increase sales turnover.